Decolonial Feminist Interventions in Metal Music - Claassen, Ilse (Tijdschrift voor Genderstudies, 2025)
Abstract This article investigates how the Indonesian female metal band Voice of Baceprot confronts persistent coloniality affecting women in contemporary Indonesia. Situated within a socio-political climate shaped by historical power imbalances and neoliberal policies, the band challenges systemic oppression through decolonial feminist interventions. The study adopts a qualitative case study design, combining a literature review, textual and musicological analysis, and reflexive thematic analysis. Framed through the theoretical concepts of coloniality, decolonial feminism, and the Distorted South, the analysis demonstrates how Voice of Baceprot disrupts patriarchal and Eurocentric norms by integrating Sundanese tonalities, vocal aggression, and subversive visual codes. In this way, the findings extend scholarship on decolonial feminist metal in postcolonial and neocolonial contexts, showing how marginalised female voices mobilise art as a site of resistance, alternative knowledge production, and identity formation.
Keywords: decolonial feminism